2003
DOI: 10.1046/j.1365-2095.2003.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of thin distillers' solubles as a palatability enhancer in rainbow trout (Oncorhynchus mykiss ) diets containing canola meal or air-classified pea protein

Abstract: Two short‐term palatability experiments indicated that supplementation of diets containing 15.0% of canola meal or 30.5% of air‐classified pea protein with 3.3% or 3.9% thin distillers' solubles (dry matter basis), respectively, increased feed intake (P < 0.05) of rainbow trout over a 4‐day period. Supplementation of the same diets with 6.6% or 1.9% thin distillers' solubles, respectively, did not increase feed intake (P > 0.05). Supplementation of the diets with 1.0% of a commercial palatability enhancer did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…Similar results have been observed for FM alternatives used in diets for other aquaculture species (Gatlin et al 2007). Feed attractants and palatability enhancers may be used to increase consumption of these alternative feedstuffs (Dias, Gomes, & Kaushik 1997;Thiessen, Campbell, & Tyler 2003;Choi et al 2004); however, flavor modifications do nothing to mitigate limitations of nutrient density or availability. Previous work with sunshine bass indicated PM protein was poorly digested (Gaylord, Rawles, & Gatlin 2004), methionine and/or lysine limiting, and an insufficient substitute for FM at 40% digestible protein (∼60% of diet, dry matter) (Gaylord & Rawles 2005).…”
supporting
confidence: 82%
“…Similar results have been observed for FM alternatives used in diets for other aquaculture species (Gatlin et al 2007). Feed attractants and palatability enhancers may be used to increase consumption of these alternative feedstuffs (Dias, Gomes, & Kaushik 1997;Thiessen, Campbell, & Tyler 2003;Choi et al 2004); however, flavor modifications do nothing to mitigate limitations of nutrient density or availability. Previous work with sunshine bass indicated PM protein was poorly digested (Gaylord, Rawles, & Gatlin 2004), methionine and/or lysine limiting, and an insufficient substitute for FM at 40% digestible protein (∼60% of diet, dry matter) (Gaylord & Rawles 2005).…”
supporting
confidence: 82%
“…Based on previously published literature and behavioral observations from the present study, palatability of treatment feeds may have been a factor. During the testing of diets and dietary constituents for various finfish species, a growth response (or lack thereof) is often attributed to palatability (e.g., red drum Sciaenops ocellatus: McGoogan and Gatlin 1997; rainbow trout Oncorhynchus mykiss: Glencross et al 2002;Thiessen and Tyler 2003). Observations from the present study indicated that bonytails fed the two shrimp diets (high and low protein) were more active feeders than fish offered the catfish and trout diets.…”
Section: Discussionmentioning
confidence: 57%
“…The digestibility in these plant sources is generally lower compared with ¢sh meal in diets of ¢sh. Attempts to improve the digestibility of plant proteins or carbohydrates have included the use of hydrothermal treatments such as extrusion, fractionation of crops to reduce the content of antinutritional factors, increase the protein concentration (Thiessen, Campbell & Adelizi 2003;Thiessen, Campbell & Tyler 2003;Venou, Alexis, Fountoulaki, Nengas, Apostolopoulou & Castritsi-Cathariou 2003) and the use of low inclusion rates of a number of plant protein sources to reduce exposure to individual antinutritional factors (Gomes, Rema & Kaushik 1995;Adelizi, Rosati, Warner, Muench, White & Brown 1998). Each of these approaches has been shown to improve the protein and energy digestibility of plant protein sources.…”
Section: Introductionmentioning
confidence: 99%